KEPEMIMPINAN PROFETIK KEPALA SEKOLAH DALAM MEMBANGUN LOYALITAS TENAGA PENDIDIK DAN KEPENDIDIKAN - Muhammad Fathur Ro'uf; Riyanto, Riyanto (JIPSKi: Jurnal Ilmu Pendidikan dan Studi Keislaman, 2023)
The world knows that Prophet Muhammad was a great dreamer. His role models and examples of his attitude in dealing with a problem are very relevant to this day. Not only that, Prophet Muhammad is also a very ideal leader. It can be seen that his attitudes can still be applied today in leading an organization or leading a group. The Islamic attitude in treating its subordinates or members is not like most leaders who only emphasize their duties and obligations. Leadership in Islam emphasizes formal and moral attitudes, not just horizontal and vertical leadership. Thus, it is certain that the relationship between leaders and members of the organization will be harmonious and will bring the organization to the peak of the ability of its members to manage the organization. The loyalty of educators and education personnel is more or less influenced by how the leader brings his organization or educational institution. Prophetic leadership that tries to emulate the attitudes of the prophet and in the Qur'an is also mentioned. As we know being honest, fair, trustworthy and always deliberating every decision making is an attitude exemplified by the Prophet Muhammad SAW for us all to emulate and contemplate. In this context, how can the leader have a prophetic leadership attitude in the educational institution he manages? This is the main problem in this paper. Keywords: Prophetic Leadership, Principal, Educators and Education Personnel, School Institutions.